2016
DOI: 10.1002/mus.25439
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Nuance: Hodgkin lymphoma presenting with Guillain–BarrÉ syndrome

Abstract: GBS preceding HL is rare, and this case highlights the importance of considering HL in the setting of GBS. Marked elevations in CSF protein, ongoing deterioration despite administration of IVIg, and constitutional symptoms with elevated inflammatory markers may be clues to possible HL-induced GBS. Muscle Nerve 55: 601-604, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
1
3
1
1
Order By: Relevance
“…9 Anderson et al describe a case where GBS was diagnosed first, and treatment with intravenous immunoglobulin resulted in worsened neurology that prompted the eventual diagnosis of lymphoma. 10 This is in contrast to our patient who responded well to intravenous immunoglobulin and recovered from GBS without any treatment directed at a potential underlying lymphoma.…”
Section: Differential Diagnosiscontrasting
confidence: 97%
“…9 Anderson et al describe a case where GBS was diagnosed first, and treatment with intravenous immunoglobulin resulted in worsened neurology that prompted the eventual diagnosis of lymphoma. 10 This is in contrast to our patient who responded well to intravenous immunoglobulin and recovered from GBS without any treatment directed at a potential underlying lymphoma.…”
Section: Differential Diagnosiscontrasting
confidence: 97%
“…Likewise, after their clinical and pathological research on GBS and Hodgkin’s lymphoma, Julien et al [14] reported a case of GBS in a patient with a relapsed phase of Hodgkin’s lymphoma. Both Anderson et al [21] and Cabot et al [16] (the latter from a case at Massachusetts General Hospital in the United States) revealed that GBS immediately preceded Hodgkin’s lymphoma, as in the present case. However, in comparison with the other previously reported cases, in this case, our patient manifested a more severe form of GBS in term of muscle power, and it was more acute to have GBS presentation after the confirmation of Hodgkin’s type lymphoma.…”
Section: Discussionsupporting
confidence: 72%
“…According to our research, only a single case-control study described a positive association between GBS and cancer [25]. Guillain-Barré syndrome is mostly associated with lymphomas [26,27]. Solid tumors associated with GBS include small cell lung cancer, breast cancer, renal cancer, hepatocellular carcinoma, tongue carcinoma, esophageal carcinoma, and the ovarian dysgerminoma.…”
Section: Discussionmentioning
confidence: 74%